2022
DOI: 10.3390/jcm11133614
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Applications of Natural Compounds in Diabetes-Associated Periodontitis

Abstract: Diabetes mellitus (DM) is a major worldwide health burden. DM is a metabolic disease characterized by chronic hyperglycemia, and if left untreated, can lead to various complications. Individuals with uncontrolled DM are more susceptible to periodontitis due to both a hyper-inflammatory host response and an impaired immune response. Periodontitis, on the other hand, may exacerbate DM by increasing both local and systemic inflammatory components of DM-related complications. The current standard for periodontal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 189 publications
0
4
0
Order By: Relevance
“…We proposed that the film extract via its functional components, Aloe vera and fibroin, acts through the common MAPK/ERK signaling pathway. Nevertheless, according to the literature, it should regulate other signaling molecules and processes involved in dynamic signaling crosstalk, such as the NF - κB signaling system. , …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We proposed that the film extract via its functional components, Aloe vera and fibroin, acts through the common MAPK/ERK signaling pathway. Nevertheless, according to the literature, it should regulate other signaling molecules and processes involved in dynamic signaling crosstalk, such as the NF - κB signaling system. , …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, according to the literature, it should regulate other signaling molecules and processes involved in dynamic signaling crosstalk, such as the NF-κB signaling system. 42,43 Our previous clinical study indicated the wound healing efficacy of the blended fibroin/aloe gel extract film. 13 The film could accelerate the healing rate of diabetic foot ulcers after application for 4 weeks, implying the sufficient delivery of the bioactive compounds from the film to the wound site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes-associated periodontal disease usually refers to diabetes-associated periodontitis (DP), a host immune response caused by interaction between periodontopathic bacteria and the host. To some degree, it aggravates diabetic complications and increases the course of periodontitis ( 2 ).…”
Section: Introductionmentioning
confidence: 99%